Unexpected 1,3-Dipolar Cycloaddition Reaction of Thiazolo[3,2-a]pyrimidine Derivatives and Nitrilimine - 李筱芳 刘浩冲 刘彬 郑爱庭 李国斌 于贤勇 易平贵 (Chinese journal of chemistry, 2011)
The 1,3-dipolar cycloaddition reactions of nitrilimine with thiazolo[3,2-a]pyrimidine derivatives was investigated. Bis-cycloadducts were obtained through a domino 1,3-dipolar cycloaddition/ring-opening/ring-opening/ 1,3-dipolar cycloaddition processes. The structures of the products were characterized thoroughly by NMR, IR, MS, elemental analysis together with X-ray crystallographic analysis.